The use of UV-induced fluorescence for the assessment of homogeneity of granular mixtures - Matuszek Dominika Barbara (Open Chemistry, 2019)
This paper presents the results of fluorescence-based analysis of homogeneity of five multicomponent granular mixtures. Analyses were performed using solutions of selected substances capable of emitting light following UV irradiation, namely Tinopal 0.03% and Rhodamine B 0.01%. Mixtures were spiked with the key component consisting of maize grains coated with the fluorescent solution. The tracer content was determined on the basis of computer image analysis, and the results were compared to those obtained using the traditional weighing method. On this basis, the proposed method was verified and assessed for applicability in estimating the homogeneity of mixtures comprised of 8, 10, 11, 14, and 20 components. The results suggest that both Tinopal and Rhodamine B may be used to estimate the tracer content in the tested mixtures.